Biblical Apocrypha in South-Eastern Europe and Related Areas (Proceedings of the Session held at the 12th International Congress of South-East European Studies [Bucharest, 2–6 September 2019]), edited by Maria Cioata, Anissava Miltenova and Emanuela Timotin. Editura Istros, Braila (2021) - Condrea, Vasile (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2022)
Biblical Apocrypha in South-Eastern Europe and Related Areas (Proceedings of the Session held at the 12th International Congress of South-East European Studies [Bucharest, 2–6 September 2019]), edited by Maria Cioata, Anissava Miltenova and Emanuela Timotin. Editura Istros, Braila (2021)